Multimedia : making it work - Vaughan, Tay (McGraw Hill Education, 2014)
"Learn the basic elements of multimedia and the skills required for a successful multimedia career from this up-to-date, full-color resource. Covering both Windows and Mac platforms, Multimedia: Making It Work, Eighth Edition explains how to incorporate text, images, sound, animation, and video into compelling projects. Hardware and software tools are described in detail. Discover how to design, organize, produce, and deliver multimedia projects on the Web, CD, and DVD. Each chapter includes full-color illustrations and screenshots, professional insights from multimedia experts, self-quizzes, and hands-on projects"